1980
DOI: 10.1007/bf00919062
|View full text |Cite
|
Sign up to set email alerts
|

Intratask distractibility in hyperkinetic and nonhyperkinetic children

Abstract: Previous laboratory studies that have either introduced extraneous enviromental stimulation or tested children in cubicles have failed to provide support for the common clinical notion that hyperkinetic children are highly distractible. Based on the Rosenthal and Allen (1978) proposal, distractibility was investigated by introducing irrelevant information within the task context. Intratask distractibility was examined by comparing the performance of hyperkinetic and nonhyperkinetic children on a speeded classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…The fact that video was arguably more salient (visual plus auditory versus auditory only) suggests that this too may explain why video was a more potent distractor for children with ADHD. In fact, previous research has demonstrated that differences between ADHD and controls emerge only for salient distractors (Rosenthal and Allen 1980). An important caveat is that there were considerable individual differences in response to the distractors (see Table 4 and Experiment 2).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The fact that video was arguably more salient (visual plus auditory versus auditory only) suggests that this too may explain why video was a more potent distractor for children with ADHD. In fact, previous research has demonstrated that differences between ADHD and controls emerge only for salient distractors (Rosenthal and Allen 1980). An important caveat is that there were considerable individual differences in response to the distractors (see Table 4 and Experiment 2).…”
Section: Discussionmentioning
confidence: 94%
“…Rosenthal and Allen (1980) and Radosh and Gittleman (1981) both showed that when highly salient distractors such as colorful pictures were used, children with ADHD were more distracted and showed greater impairment on task performance than did control children. Of note is that only the highly salient distractors had this effect; distractors that were less salient did not change the children's performance.…”
mentioning
confidence: 94%
“…Alternatively, investigators could select subjects basely solely on the reports of a single informant. This strategy would exclude some children with ADHD who are symptomatic in one situation only and would not permit a distinction between situational and pervasive ADHD (e.g., Atkins, Pelham, & Licht, 1985;Dykman, Ackerman, & Oglesby, 1979;Goldstein, 1987aGoldstein, , 1987bRosenthal & Allen, 1980;Sergeant & Scholten, 1985a, 1985b.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions children with ADHD choose the more stimulating alternative (Lee & Zentall, 2002). In general, added "bells and whistles" can decrease the performance of children with ADHD more than for their peers when that stimulation is nonrelevant and is added within complex tasks or is added externally in such a way that attention cannot be shared and performance is timed (Rosenthal & Allen, 1980;Zentall, Zentall, & Barack, 1978a;Zentall, Zentall, & Booth, 1978b).…”
Section: Selective Inattentionmentioning
confidence: 97%